Chlorination or monochloramination: Balancing the regulated trihalomethane formation and microbial inactivation in marine aquaculture waters - Sanawar, H.; Xiong, Y.; Alam, A.; Croue, Jean-Philippe; Hong, P. (Elsevier BV, 2017)
Disinfection methods like chlorination are increasingly used to sanitize the water, equipment, tools and surfaces in aquaculture facilities. This is to improve water quality, and to maintain a hygienic environment for the well-being of aquatic organisms. However, chlorination can result in formation of regulated disinfection byproducts (DBPs) that can be carcinogenic and toxic. This study aims to evaluate if an optimal balance can be achieved between minimal regulated DBP formation and effective microbial inactivation with either chlorination or monochloramination for application in the Red Sea aquaculture waters. Upon chlorination, the concentration of total trihalomethanes (THMs), primarily bromoform, exceeded the regulatory limit of 80 µg/L even at the lowest tested concentration of chlorine (1 mg/L) and contact time (1 h). Comparatively, regulated THMs concentration was only detectable at 30 µg/L level in one of the three sets of monochloraminated marine aquaculture waters. The average log reduction of antibiotic-resistant bacteria (ARB) by chlorine ranged from 2.3-log to 3.2-log with different contact time. The average log reduction of ARB by monochloramine was comparatively lower at 1.9 to 2.9-log. Although viable Staphylococcus aureus was recovered from monochloraminated samples as opposed to chlorinated samples, the abundance of S. aureus was not high enough to result in any significant microbial risks. Both chlorination and monochloramination did not provide any significant improvement in the reduction of antib iotic resistance genes (ARGs). This study demonstrates that a systematic evaluation is needed to determine the optimal disinfectant required to balance both microbial and chemical risks. Compared to chlorine, monochloramine may be a more appropriate disinfection strategy for the treatment of aquaculture effluents prior to discharge or for recirculatory use in the aquaculture facility.